Structural and magnetic properties of quasi-one-dimensional doped LiCuVO4 - Kumar A.; Kumari P.; Das A.; Dwivedi G.D.; Shahi P.; Shukla K.K.; Ghosh A.K.; Nigam A.K.; Chattopadhyay K.K.; Chatterjee S. (My University, 2025)
The Neutron diffraction, X-ray photoemission and Magnetic properties of Zn, Co and Mn-doped LiCuVO4 were investigated. Both with Zn and Co doping the antiferromagnetic correlation increase. On the other hand Mn-doping induces the short range ferromagnetic ordering. Neutron diffraction study does not show any phase transition down to 5 K i.e., there is no indication of long range magnetic ordering. Neutron diffraction study also indicates that with Zn, Co and Mn doping the V-O lengths are changed. Maximum change in the V-O distances is observed for Mn-doped sample. On the other hand, X-ray photoemission spectroscopic data indicates Mn doping converts some Cu 2+ ions into Cu3+ ions. © 2013 Published by Elsevier Inc.